(untitled) (Research, Society and Development, 2022)
Objective: To know the family’s challenges in the face of mental disorder. Method: This study is an integrative review of the literature, bringing 6 steps, 1st identification of the theme, 2nd establishment of inclusion and exclusion criteria, 3rd definition of information to be extracted from the selected studies, 4th evaluation of the studies, 5th interpretation of results and 6th presentation of the study review. Result: It is observed that the family of the person with mental disorder develops important actions in care, facing difficulties in daily care and that they need family inclusion within the health services to be heard and find support for coping with the disorder. Conclusion: The mental disorder affects the family nucleus and the emotional state of the entire family network, the family is weakened and generates a physical, emotional and financial burden. Even though they feel overwhelmed, they feel satisfaction in caring for the patient. Families need to be heard, to have a space to share their experiences and anxieties, such as the relationship with the sick family member and the strategies for coping with the disease. There is a need to have a family inclusion to be made by professionals in the mental health area, allowing open spaces for family members and for people with mental disorders. Thus providing a space that offers a better understanding of the disease and how to act in times of crisis.